Steady-State Plasma Pharmacokinetics of Oral Voriconazole in Obese Adults - Pai, Manjunath P. (American Society for Microbiology, 2011)
Voriconazole is an antifungal agent that is currently used as primary therapy for invasive aspergillosis and as a potential treatment for systemic candidiasis. Data on the dosing of voriconazole in obese patients are not available, which is problematic given the increased prevalence of this special population. To address this limitation, we evaluated the steady-state plasma pharmacokinetics of voriconazole through a two-way, crossover design in a cohort of eight healthy volunteers with class II obesity or greater. The median (minimum, maximum) age, weight, and body mass index of obese subjects were 43 (22, 48) years, 133 (105, 155) kg, and 46.2 (38.4, 53.7) kg/m(2), respectively. The geometric mean ratios (90% confidence intervals) for the area under the curve from time zero to 12 h (dosing interval; AUC(0–τ)), maximum concentration (C(max)), minimum concentration at 12 h (C(min)), and time to C(max) (T(max)) of the 300-mg to 200-mg dosing regimens were 2.0 (1.5, 2.7), 1.8 (1.4, 2.2), 2.2 (1.6, 2.9), and 1.6 (1.0, 2.4) in obese subjects, respectively. The AUC(0–τ) values observed in obese subjects were comparable to those from a historical data set of nonobese subjects. Voriconazole dose-normalized AUC(0–τ) values had a modestly better correlation with lean body weight (r(2) = 0.42) than total body weight (r(2) = 0.14). An excellent linear relationship (r(2) = 0.96) was identified between C(min) values and AUC(0–τ) values. Adjustment of voriconazole doses in individuals with class II obesity or greater does not appear to be necessary on the basis of body weight.